Correction: Computational reassessment of RNA-seq data reveals key genes in active tuberculosis. - Rakesh Arya; Hemlata Shakya; Reetika Chaurasia; Surendra Kumar; Joseph M Vinetz; Jong Joo Kim (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0305582.].